Vulnerability of RC buildings and risk assessment for Cyprus - Kyriakides, Christopher; Pilakoutas, Kypros; Chrysostomou, Christis (My University, 2010)
The work described in this paper is part of the doctoral thesis of Kyriakides1, which examines the various steps towards the derivation of probabilistic analytical vulnerability curves using Cyprus as a case study. The part included in this paper focuses on two main objectives of the work which are the use of analytical results for the prediction of the structural response of RC buildings for various hazard levels and the quantification of the damage potential for the predicted structural response. Initially, the most reliable capacityspectrum method is chosen to arrive at the estimation of the structural response. The accuracy of this procedure is demonstrated against "exact" values obtained from timehistory analysis and results from an alternative capacity-spectrum procedure. In addition a revised idealisation technique for the bilinearisation of the capacity envelope referred to as equivalent elastic-perfectly plastic system (ES) technique is proposed. A simulation study is conducted to assess the accuracy of this technique compared to the 'exact' results from dynamic nonlinear time-history analysis. Subsequently a damage index, to correlate structural response to damage potential, is selected based on a number of criteria.
Keywords: Analytical vulnerability methods; Capacity curve; Capacity spectrum methods; Damage index